Enhancing attitude towards e-waste management through environmental health education among electronic technicians in Ibadan, Oyo State Nigeria (2017)
Health hazard of e-waste is emerging as alarming public health problem in Nigeria. E- wastes are generated in an increased manner because electrical and electronic equipment purchased originally as second hand reached its end-of-life rapidly. Disposal of e-waste is done using unsanitary methods due to poor attitude of electronic technicians to e-waste management. This study sought to enhance attitude towards e-waste management through environmental health education among electronic technicians in Oyo State, Nigeria. A pretest-post test control group quasi-experimental research design was adopted for this study. Purposive and systematic sampling techniques were used to select one hundred participants. Three research hypotheses were tested at 0.05 alpha level. Data collected were analysed using Multivariate Analysis of Covariance (MANCOVA). Findings revealed that, there was a significant main effect of treatment on attitude towards e-waste management among electronic technicians in Ibadan Oyo State, Nigeria. [F(1.84)=4.900, p<0.05, η2=0.055). Based on the finding, it was recommended that environmental health education should be organised for electronic technicians.